2003
DOI: 10.1007/s10072-003-0103-5
|View full text |Cite
|
Sign up to set email alerts
|

123I-Ioflupane/SPECT binding to striatal dopamine transporter (DAT) uptake in patients with Parkinson’s disease, multiple system atrophy, and progressive supranuclear palsy

Abstract: We used SPECT and the tracer (123)I-Ioflupane to measure dopamine transporter (DAT) binding in the caudate nucleus and the putamen of 70 patients with Parkinson's disease (PD), 10 with multiple system atrophy (MSA-P type), and 10 with progressive supranuclear palsy (PSP). Data were compared with 12 age-matched control subjects. We found significant reductions in mean striatal values in all three forms of parkinsonism. However, decrements were significantly greater in PSP (0.51+/-0.39, p<0.01) compared with MSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 7 publications
7
86
0
1
Order By: Relevance
“…On early phase images, a decrease or increase of regional uptake is shown in MSA-P, MSA-C, PSP, and DLB groups compared with the IPD group. These findings generally correspond with several previous studies that have identified characteristic DAT binding of neurodegenerative parkinsonism [32][33][34] and glucose metabolism patterns with IPD, MSA, PSP, and DLB [11,23,26,27], respectively. NA not applicable…”
Section: Discussionsupporting
confidence: 92%
“…On early phase images, a decrease or increase of regional uptake is shown in MSA-P, MSA-C, PSP, and DLB groups compared with the IPD group. These findings generally correspond with several previous studies that have identified characteristic DAT binding of neurodegenerative parkinsonism [32][33][34] and glucose metabolism patterns with IPD, MSA, PSP, and DLB [11,23,26,27], respectively. NA not applicable…”
Section: Discussionsupporting
confidence: 92%
“…However, the putamen/caudate ratio is greater in APS than in PD, suggesting a more uniform dopamine depletion both in putamen and in caudate nucleus in APS patients; this result concurs with the previously discussed visual assessment. Two more studies verify that there is more symmetric loss of dopaminergic nerve terminals in MSA [35] and in PSP [36] compared to PD. This finding could depend on higher severity of clinical symptoms in APS patients at the time of the first clinical evaluation.…”
Section: Datscanmentioning
confidence: 89%
“…On the contrary, in PSP DAT imaging (putamen-to-caudate ratio) suggests a more uniform involvement of dopamine nerve terminals in both caudate nucleus and putamen 29 . In Fig 3 we highlight an illustrative brain SPECT imaging using TRODAT-1 as the radiopharmaceutical in a PSP-P subject matched for age and gender to a healthy control subject.…”
Section: Molecular Imaging (Dopaminergic Binding Sites)mentioning
confidence: 92%